KiwiSaver and Retirement Adequacy - Kirsten L MacDonald; Robert J. Bianchi; Michael E. Drew (Australasian Accounting, Business and Finance Journal, 2012)
Investors face a long and uncertain journey to retirement and beyond, particularly when investing in new defined contribution schemes such as New Zealand’s KiwiSaver. This paper seeks to provide positive insights into the design of KiwiSaver by assessing the recently announced move from 4 to 6% minimum contribution rates using stochastic simulation. We consider retirement adequacy from two perspectives: (i) multiples of gross final earnings achieved during the accumulation phase; and (ii) replacement rates of salaries during the decumulation phase. The findings reveal that an increase in the contribution rate from 4 to 6% dramatically increases the probability of investors reaching a retirement target of eight (8) times final earnings, from 6% to 40%. However, despite the shift in lifetime contributions in the right direction, the simulation analysis suggests that, in the majority of scenarios, KiwiSaver investors will not achieve an adequate retirement target.
Keywords: KiwiSaver; retirement outcomes; contribution rates